INSURABILITY OF PUNITIVE DAMAGES - A LEGAL PERSPECTIVE - Hultquist, Michael D. (Assurances)

(untitled) (HEC Montréal, 2002)
Under the theme of the insurability of punitive damages, this article is a study, from a legal, marketing and underwriting perspective in the United States, varying from state to state. Like a casualty risk, insurers can identify target industries and build statistical models involving punitive damages. The author reviews the law of insurability of punitive damages, including the varying analyses applied in determining which law controls a potential dispute regarding the insurability of punitive damages, and some suggestions for insurers and companies interested in punitive damage coverage.